Substrate Specificities and Inhibition Pattern of the Solute Carrier Family 10 Members NTCP, ASBT and SOAT - Grosser, Gary; Müller, Simon Franz; Kirstgen, Michael; Döring, Barbara; Geyer, Joachim (Frontiers in Molecular Biosciences, 2021)
Three carriers of the solute carrier family SLC10 have been functionally characterized so far. Na+/taurocholate cotransporting polypeptide NTCP is a hepatic bile acid transporter and the cellular entry receptor for the hepatitis B and D viruses. Its intestinal counterpart, apical sodium-dependent bile acid transporter ASBT, is responsible for the reabsorption of bile acids from the intestinal lumen. In addition, sodium-dependent organic anion transporter SOAT specifically transports sulfated steroid hormones, but not bile acids. All three carriers show high sequence homology, but significant differences in substrate recognition that makes a systematic structure-activity comparison attractive in order to define the protein domains involved in substrate binding and transport. By using stably transfected NTCP-, ASBT-, and SOAT-HEK293 cells, systematic comparative transport and inhibition experiments were performed with more than 20 bile acid and steroid substrates as well as different inhibitors. Taurolithocholic acid (TLC) was identified as the first common substrate of NTCP, ASBT and SOAT with Km values of 18.4, 5.9, and 19.3 µM, respectively. In contrast, lithocholic acid was the only bile acid that was not transported by any of these carriers. Troglitazone, BSP and erythrosine B were identified as pan-SLC10 inhibitors, whereas cyclosporine A, irbesartan, ginkgolic acid 17:1, and betulinic acid only inhibited NTCP and SOAT, but not ASBT. The HBV/HDV-derived myr-preS1 peptide showed equipotent inhibition of the NTCP-mediated substrate transport of taurocholic acid (TC), dehydroepiandrosterone sulfate (DHEAS), and TLC with IC50 values of 182 nM, 167 nM, and 316 nM, respectively. In contrast, TLC was more potent to inhibit myr-preS1 peptide binding to NTCP with IC50 of 4.3 µM compared to TC (IC50 = 70.4 µM) and DHEAS (IC50 = 52.0 µM). Based on the data of the present study, we propose several overlapping, but differently active binding sites for substrates and inhibitors in the carriers NTCP, ASBT, SOAT.